From Micromagnetic to In Silico Modeling of Magnetic Nanodisks for Hyperthermia Applications. Issue 5 (26th March 2021) - Manzin, Alessandra; Ferrero, Riccardo; Vicentini, Marta
Abstract: Magnetic nanodisks have been recently proposed as biomedical tools for therapeutics at the nanoscale level, with a special focus on hyperthermia for cancer cure. Here we present a detailed study of permalloy nanodisks to be used in alternative to superparamagnetic iron oxide nanoparticles, as efficient heating agents that release heat via magnetic hysteresis. A micromagnetic modeling analysis is carried out to identify sizes and ac field parameters that maximize the specific loss power (SLP), guaranteeing the fulfillment of biophysical constraints (Hergt–Dutz limit) and vortex state at remanence (reduced agglomeration effects). The highest SLP (790 W g −1 ) is found for 100 nm diameter and 20 nm thickness nanodisks, excited at a frequency of 75 kHz. Further analysis elucidates the influence of magnetostatic interactions and local nanodisk‐field orientation on the SLP of nanodisk clusters, which originate from the deposition in target tissues. At high concentrations, magnetostatic interactions can lead to a reduction of 40–50% in the hysteresis losses. From thermal simulations, we finally demonstrate that in a murine model temperature increments comparable to that obtained in calorimetric measurements under quasi‐adiabatic conditions can be achieved only by using an order of magnitude larger dosage of nanodisks, due to blood perfusion effects. Abstract : A micromagnetic modeling analysis is performed to explore permalloy nanodisks as heating agents in magnetic hyperthermia and identify sizes and field parameters that maximize energy losses, enabling biophysical constraint fulfillment and agglomeration effect reduction. Magnetostatic interactions in nanodisk clusters are also investigated. Thermal simulations in a murine model are finally carried out to provide indications about effective dosage and side‐effects.